2007
DOI: 10.3748/wjg.v13.i2.294
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of recombinant hepatitis B virus vaccine in patients with and without chronic hepatitis C virus infection: A case-control study

Abstract: Immunogenicity of recombinant hepatitis B virus vaccine in patients with and without chronic hepatitis C virus infection:A case-control study. World J Gastroenterol 2007; 13(2): 294-298http://www.wjgnet.com/1007-9327/13/294.asp INTRODUCTIONOne major transmission route for both hepatitis C virus (HCV) and hepatitis B virus (HBV) is the parenteral route, and the sources of infection include administration of blood or blood products [1,2] , intravenous drug use [3,4] and needle-stick accidents [5,6] . Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Las tasas de seroconversión alcanzadas con la vacunación para el VHB en pacientes con EHC varían ampliamente y dependen sobre todo del grado de disfunción hepática. Así, en pacientes con HC por VHC estas tasas oscilan entre el 69 y el 88,5% [21][22][23][24] . Incluso si se emplean dosis mayores (40 mg) y con una pauta acelerada (0, 1 y 2 meses), los resultados son similares (80%) 25 .…”
Section: Discussionunclassified
“…Las tasas de seroconversión alcanzadas con la vacunación para el VHB en pacientes con EHC varían ampliamente y dependen sobre todo del grado de disfunción hepática. Así, en pacientes con HC por VHC estas tasas oscilan entre el 69 y el 88,5% [21][22][23][24] . Incluso si se emplean dosis mayores (40 mg) y con una pauta acelerada (0, 1 y 2 meses), los resultados son similares (80%) 25 .…”
Section: Discussionunclassified
“…Two small studies (14,19) reported no significant difference between HCV and healthy cohorts in response to HBV vaccination. Daryani et al (27) found that chronic HCV infection lost its significant correlation to vaccine response when smoking was in the model. In one of the larger studies, using a nonstandard HBV dose and schedule, a significantly lower response was found in individuals with cirrhosis compared with controls and noncirrhotic chronic HCV individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Daryani et al (27) compared the response of standard HBV vaccination between patients with chronic HCV confirmed by HCV-RNA and healthy controls. Although a statistically significant difference in vaccine response was observed between those chronically infected with HCV and controls on univariate analysis (73.7% versus 95%), on multivariate analysis, smoking was a significant confounder and when introduced into the model HCV infection, lost its significant correlation with lower antibody response.…”
Section: Hbv Vaccinationmentioning
confidence: 99%
“…4 In patients with CHC, the immunogenicity of the HBV vaccine has been investigated in several studies including adults, and in some the response to the vaccine is reduced. [5][6][7][8][9][10][11][12] This study reports the rate of response to the HAV and HBV vaccines, duration of protection and the incidence of acute HAV or HBV infections during follow-up in patients with CHC compared with healthy controls.…”
Section: Introductionmentioning
confidence: 99%